MASALAH - MASALAH YANG DIALAMI OLEH SISWA DI MADRASAH ALIYAH NEGERI KUOK T.P 2015/2016 - Darmawati '; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is aimed at 1) finding out the male and female students' personal problems; 2) finding out the male and female students' emotional problems; 3) finding out the male and female students’ learning problems; 4) finding out the male and female students' familial problems; 5) finding out the male and female students' social problems; 6) finding out the overall problems faced by male and female students; 7) finding out the most dominant category of students' problems in general. The subjects of the research are 200 11th and 12th grade students of Kuok State Islamic Senior High School. The sampling technique is the total one, therefore the entire population were taken as samples. There are no greater written subjects or groups because entire individuals in a group are involved directly, hereafter this kind of sampling technique is called total sampling (Ibnu Jahar, 1999). The research results showed that: 1) more female students experienced personal problems than male students. While, the personal problems experienced by male students were emotional ones; 2) more male students experienced emotional problems than female students, in other words female students experienced less emotional problems; 3) more male students experienced learning problems than female students, in other words female students experienced less learning problems; 4) more male students experienced social problems than female students in other words female students experienced less social problems; 5) more male students experienced familial problems than female students in other words female students experienced less familial problems; 6) in general, male and female students experienced more personal and social problems. The personal problems experienced by male and female students caused their difficult learning concentration; 7) the problems experienced by students were generally categorized moderate.Keywords: Students’ problems